2008
DOI: 10.1111/j.1551-2916.2007.02212.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Bagasse Ash as a Potential Quartz Replacement in Red Ceramic

Abstract: Sugarcane bagasse ash (SCBA) is an industrial waste that contains silicon and aluminum oxides as the major components and iron, calcium, magnesium, and potassium oxides as the main minor components. In this paper, SCBA from one Brazilian factory was characterized and tested for its influence on the ceramic properties of clay/ash ceramic probes. Prismatic probes were pressed (18 MPa) using a ceramic mass mixed with 0%, 5%, 8%, and 10% ash. The probes were fired at temperatures between 800° and 1200°C. X‐ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
2
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(53 citation statements)
references
References 16 publications
1
38
2
12
Order By: Relevance
“…Tal disponibilidade pode ser atribuída ao processo de mineralização do bagaço da cana durante o processo de compostagem que, provavelmente, possibilitou a solubilização do Si contido neste material, estando prontamente disponível quando da sua aplicação ao solo. Já os compostos CS e SA, embora apresentem teores de Si total mais elevados (Tabela 2) em virtude da presença de sílica gel contida no bagaço de cana (BC) (Savat et al, 1999) e de sílica cristalina presente no quatzo da cinza de bagaço de cana (CBC) (Teixeira et al, 2008), sofreram pouca influência das doses empregadas. Essas diferentes formas de silício se combinaram, provavelmente, formando ácido polissilíssico, durante o processo de compostagem.…”
Section: Silício "Disponível"unclassified
“…Tal disponibilidade pode ser atribuída ao processo de mineralização do bagaço da cana durante o processo de compostagem que, provavelmente, possibilitou a solubilização do Si contido neste material, estando prontamente disponível quando da sua aplicação ao solo. Já os compostos CS e SA, embora apresentem teores de Si total mais elevados (Tabela 2) em virtude da presença de sílica gel contida no bagaço de cana (BC) (Savat et al, 1999) e de sílica cristalina presente no quatzo da cinza de bagaço de cana (CBC) (Teixeira et al, 2008), sofreram pouca influência das doses empregadas. Essas diferentes formas de silício se combinaram, provavelmente, formando ácido polissilíssico, durante o processo de compostagem.…”
Section: Silício "Disponível"unclassified
“…The chemical composition of SCBA may be different depending on the type of sugar cane and composition of the soil where it is cultivated. The X-ray diffraction (XRD) data for SCBA shows patterns that suggest that the major crystalline phase is quartz (Teixeira et al 2008), corresponding to the SiO 2 fraction demonstrated in the chemical analysis (Fig. 9).…”
Section: Ashe Characterization and Charcoal Separationmentioning
confidence: 96%
“…Fly ash contains more charcoal than the bottom ash, and nowadays, in the most modern factories the bottom ash is mixed with the fly ash inside the water channel that comes from the gas washer. The inorganic fraction can be used by the ceramic industry (Teixeira et al, 2008) as non-plastic material to produce bricks and roof tiles, to produce glass-ceramic materials (Teixeira et al, 2010b) or as pozzolan in cementitious materials (Frías et al 2011;Dutta and Das 2010;Cordeiro et al 2009). …”
Section: Ashes From Sugarcane Bagassementioning
confidence: 99%
“…A quantidade de resíduo de cinzas de bagaço de cana-de-açúcar (RCBCA) gerada corresponde à cerca de 0,5 % em peso, em relação à massa inicial do bagaço. Estima-se que no Brasil sejam produzidas nas usinas de açúcar e álcool cerca de 1.200.000 toneladas/ano de RCBCA [2][3][4]. Por outro lado, o RCBCA não tem uma utilização definida para a indústria da cana-de-açúcar.…”
Section: Introductionunclassified